Comprehensive Volumetric Analysis of Mecp2-Null Mouse Model for Rett Syndrome by T2-Weighted 3D Magnetic Resonance Imaging - Akaba, Yuichi; Shiohama, Tadashi; Komaki, Yuji; Seki, Fumiko; Ortug, Alpen; Sawada, Daisuke; Uchida, Wataru; Kamagata, Koji; Shimoji, Keigo; Aoki, Shigeki; Takahashi, Satoru; Suzuki, Takeshi; et al. (Frontiers in Neuroscience, 2022)
Rett syndrome (RTT) is a severe progressive neurodevelopmental disorder characterized by various neurological symptoms. Almost all RTT cases are caused by mutations in the X-linked methyl-CpG-binding protein 2 (MeCP2) gene, and several mouse models have been established to understand the disease. However, the neuroanatomical abnormalities in each brain region of RTT mouse models have not been fully understood. Here, we investigated the whole and detailed neuroanatomy of the Mecp2 gene-deleted RTT model (Mecp2-KO) mouse brain using T2-weighted 3D magnetic resonance imaging with different morphometry to clarify the brain structural abnormalities that are involved in the pathophysiology of RTT. We found a significant reduction in whole and almost all regional volumes in the brain of Mecp2-KO mice. In addition, a detailed comparative analysis identified specific volume reductions in several brain regions in the Mecp2-deficient brain. Our analysis also revealed that the Mecp2-deficient brain shows changes in hemispheric asymmetry in several brain regions. These findings suggest that MeCP2 affects not only the whole-brain volume but also the region-specific brain structure. Our study provides a framework for neuroanatomical studies of a mouse model of RTT.